Metamorphosis – An Environment to Achieve Semantic Interoperability with Topic Maps - Librelotto, Giovani Rubert; Ramalho, José Carlos; Henriques, Pedro Rangel (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2006: Anais do III Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2006.14741, 2006)
Nowadays, data handled by an institution or company is spread out by more than one database and lots of documents of different types. To extract the information implicit in that data, it is necessary to pick parts from those various archives. To obtain a general overview, those information slices should be gather. Different approaches can be followed to achieve that integration, ranging from the merge of resources till the fusion of the extracted parts. In this paper, we introduce Metamorphosis – a Topic Maps oriented environment to generate conceptual navigators for heterogenous information systems – and we argue that Metamorphosis can be used to achieve the referred interoperability.